A novel homozygous variant in SLC25A46 gene associated with pontocerebellar hypoplasia type 1E: a case report - Guillaume, Adrien; Stejskal, Vojtech; Smits, Guillaume; Kelen, Dorottya (Frontiers in Pediatrics, 2024)
Neonatal encephalopathy (NE) is a complex clinical condition with diverse etiologies. Hypoxicischemic encephalopathy (HIE) is a major contributor to NE cases. However, distinguishing NE subtypes, such as pontocerebellar hypoplasia type 1E (PCH1E), from HIE can be challenging due to overlapping clinical features. Here, we present a case of PCH1E in a neonate with a homozygous mutation c.72delT p. (Phe24LeufsTer20) in the SLC25A46 gene. The severity of PCH1E associated NE highlighted the significance of early recognition to guide appropriate clinical management.